PS-3 Effects of Feeding Rates on Diflubenzuron Efficacy Against Filth Flies (Diptera: Muscidae) in Manure of Beef Heifers. (22nd October 2022) - Martin, Emma C; Sanchez-Sandoval, Ulises A; Ramirez, Jovannah; Smythe, Brandon G
Abstract: The objective of the current study is to determine the effect of feeding rates on the efficacy of diflubenzuron against filth fly development in the manure of beef heifers. Twelve Angus × Hereford crossbred heifers (263 kg ± 16.2 kg BW) were used in a completely randomized design and heifers were assigned to a 2 x 2 factorial arrangement of treatments to evaluate the efficacy of diflubenzuron against horn flies Haematobia irritans (L.), stable flies Stomoxys calcitrans and house fly Musca domestica utilizing fecal bioassays. Treatments consisted of 2 insecticidal treatments [Diflubenzuron (DFB; 0.10 mg per kg BW) and no DFB (CNT)] in a factorial arrangement with 2 dietary fed regimens [1.5% BW alfalfa hay cubes and 3.0% BW alfalfa hay cubes]. All heifers receiving DFB treatments were dosed daily beginning on day 0 and continuing through day 7. Manure samples were collected daily prior to DFB offering and for 11 consecutive days. Efficacy calculations were developed utilizing standard filth fly fecal bioassays accounting for control performance. A treatment × day interaction (P ≤ 0.01) was observed for all species largely associated with the presence of DFB and associated with the on-set of efficacy (day 0–2) and wash out (day 8–10) of the product. Feeding regimen did not (P > 0.05) influence DFB performance against any of the fly species evaluated. Formulations of DFB appear to handle a wide range of animal intake scenarios under controlled situations.